Evaluation of the Impact Strength and Morphology Properties of Musa Acuminata Fiber Composite/CaCo3 Powder - Nasmi Herlina Sari; Salman; Suteja; Yusuf Akhyar Sutaryono; Joni Iskandar (Journal of Fibers and Polymer Composites, 2023)
Banana stem (Musa Acuminata, MA) fiber is a free agricultural waste obtained after harvesting the fruit. When compared to synthetic fibers, banana fiber has significant weaknesses in composite production, such as low interfacial bond strength between the fiber and the matrix. The purpose of this research is to improve the impact strength of banana stem fiber composites by adding CaCO3 powder. The hot press technique is used to create composites. In the production of polyester composites, woven MA and CaCO3 stem fibers are prepared. An impact testing machine and a scanning electron microscope were used to investigate the effect on morphological properties and impact strength. The study's findings revealed that a polyester composite containing 10% banana stem fiber and 25% CaCO3 had the highest impact strength of 45.27 KJ/m2, which was associated with strong adhesion between the CaCO3-fiber and the polyester matrix. Fiber pullout, matrix cracking, and fiber debonding were all observed in the composite fracture morphology. The resulting composite properties could be used to replace palm fiber/fiber glass composites.